2010
DOI: 10.1007/s11746-009-1535-8
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Binding of Off‐Flavor Compounds with Soy Protein and β‐Cyclodextrin in a Ternary System: A Model Study

Abstract: Removal of soy protein (SP)-bound 2-nonanone by b-cyclodextrin (bCD) was studied using an equilibrium dialysis technique. It was observed that in the presence of bCD, a significant (p \ 0.05) amount of SP-bound 2-nonanone could be removed in a concentration-dependent manner. Up to 94% of SP-bound 2-nonanone was stripped from SP when 6 mM bCD was present in the system. However, in thermodynamic terms, the net standard free energy change for transfer of 2-nonanone from SP to bCD, i.e., DDG SP!bCD , was essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 33 publications
(36 reference statements)
1
14
1
Order By: Relevance
“…In a previous report, we demonstrated that b-cyclodextrin (bCD) forms an inclusion complex with 2-nonanone and suggested that this approach could be equally effective in removing SP bound off-flavor volatiles with an alkyl chain of medium length (less than nine carbons) [16]. Here, we extend the same argument by hypothesizing that bCD could form inclusion complexes with SP-bound PLs and effectively extract them into the aqueous phase.…”
Section: Introductionsupporting
confidence: 58%
“…In a previous report, we demonstrated that b-cyclodextrin (bCD) forms an inclusion complex with 2-nonanone and suggested that this approach could be equally effective in removing SP bound off-flavor volatiles with an alkyl chain of medium length (less than nine carbons) [16]. Here, we extend the same argument by hypothesizing that bCD could form inclusion complexes with SP-bound PLs and effectively extract them into the aqueous phase.…”
Section: Introductionsupporting
confidence: 58%
“…Compared with animal proteins, less emphasis has been put on plant or vegetable proteins. Soy proteins have been the most popular plant proteins used in flavour binding studies due to the presence of beany or grassy off‐flavours from lipoxygenase‐catalysed oxidation of unsaturated fatty acids . Pulse proteins are rarely studied; only pea protein and fababean protein have been evaluated.…”
Section: Flavour‐food Matrix Interaction and Flavour Perceptionmentioning
confidence: 99%
“…Soy proteins have been the most popular plant proteins used in flavour binding studies due to the presence of beany or grassy off-flavours from lipoxygenase-catalysed oxidation of unsaturated fatty acids. [6,27,28,[40][41][42] Pulse proteins are rarely studied; only pea protein [7,43] and fababean protein [44,45] have been evaluated. There have been no data reported for canola protein.…”
Section: Source Of Proteins and Flavours Used In Previous Studiesmentioning
confidence: 99%
“…The major physical deodorization is embedding with β-cyclodextrin (β-CD) which is hydrolyzed by gastric acid and digested easily (Shieh and Hedges, 1996). The fact that β-CD has been approved as a safe ingredient for food applications makes β-CD a promising candidate for removing off-flavors (Arora and Damodaran, 2010). β-CD, containing peculiar hydrophobic cavum, can form inclusion complexes with various off-flavor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…β-CD, containing peculiar hydrophobic cavum, can form inclusion complexes with various off-flavor molecules. Previously, β-CD was used to remove volatile beany flavor compounds from soy milk (Arora and Damodaran, 2010). The chemical deodorization is taken no consideration due to its chemical residues.…”
Section: Introductionmentioning
confidence: 99%